Effectiveness and safety of acupuncture for Parkinson’s disease anxiety: a systematic review and meta-analysis - Chen, Lu; Xu, Hong-xiao; Wang, Zhao-qin; Li, Guo-na; Wu, Lu-yi; Huang, Yan; Wu, Huan-gan; Zhou, Jian-hua (Frontiers in Aging Neuroscience, 2025)
BackgroundIndividuals with Parkinson’s disease (PD) commonly experience anxiety, with a prevalence of 31%. This study systematically evaluates the efficacy and safety of acupuncture for anxiety related to PD.MethodNine databases were searched for randomized controlled trials (RCTs) published from inception to August 24, 2025. RCTs comparing acupuncture and moxibustion treatments (with or without other therapies, e.g., western medicine, routine care, sham acupuncture) to other therapies alone for managing PD anxiety were included. Data were analyzed using the R software (version 4.5.1). In accordance with PRISMA-2020 guidelines, two reviewers independently extracted data and assessed the risk of bias using the Cochrane risk of bias tool (ROB 2.0). The certainty of the evidence was graded using the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) according to GRADE handbook.ResultsA total of 10 studies were included, comprising 1,000 patients with anxiety after PD. The meta-analysis indicated that, compared to the control group, the acupuncture group showed significant improvements in HAMA and SAS scores (SMD = −3.64, 95% CI [−5.06 to −2.23]; SMD = −7.76, 95% CI [−10.10 to −5.41]), as well as significant improvements in HAMD and SDS scores (SMD = −2.93, 95% CI [−4.25 to −1.60]; SMD = −8.35, 95% CI [−8.88 to −7.82]). The reported adverse events related to acupuncture were minimal and less severe.ConclusionAcupuncture can successfully reduce anxiety symptoms in PD patients. Additional higher quality randomized controlled trials are required to ascertain the safety and effectiveness of acupuncture as a therapy for anxiety in PD patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, Identifier CRD42024601125.